Determinants of Cytochrome P450 2D6 mRNA Levels in Healthy Human Liver Tissue - Miaoran Ning; Julio D. Duarte; Faith Stevison; Nina Isoherranen; Leah H. Rubin; Hyunyoung Jeong (Wiley, 2019)
Cytochrome P450 2D6 (CYP2D6) is a major drug‐metabolizing enzyme that exhibits large interindividual variability. Recent studies suggest that differential transcriptional regulation of CYP2D6 in part may be responsible for the variability. In this study, we characterized potential determinants of CYP 2D6  transcript levels in healthy human liver tissue samples (n = 115), including genetic polymorphisms in CYP2D6 and the genes encoding transcription regulators for CYP2D6 expression; mRNA expression of the transcription factors and their known target genes; and hepatic levels of bile acids and retinoids, agents that modulate the expression/activity of the transcription factors. Their associations with CYP2D6 mRNA levels in the tissues were examined. Results from multivariable linear regression analysis revealed CYP8B1 mRNA level and rs3892097, the single‐ nucleotide polymorphism defining the nonfunctional CYP2D6*4 allele, as the two most significant predictors of CYP2D6 mRNA levels in the liver tissue samples, explaining 30% of the variability.